POWER RELATIONS ON FEMALE BODY IN SENO GUMIRA AJIDARMA’S SHORT STORY - Sulistya Ningtyas (POETIKA, 2021)
This study explored the practice of power relations and the panopticon as a disciplinary mechanism in Seno Gumira Ajidarma’s Istana Tembok Bolong short story. ‘Istana tembok bolong’ in this literary work refers to a place near a train station that is separated from the outside area by a perforated wall, which turns to be a palace for the lower class of society occupying the space. By using Foucauldian analysis, this study examined the case of ‘selling matches’ as the central issue of the story being discussed. This phenomenon that occurred in Yogyakarta in the 1970s became the media of the manifestation of power over street prostitutes. The results showed that power relations operate as a means to control the body, particularly female bodies. This is because female bodies become commodities as a result of capitalism. However, in a certain situation, these street prostitutes can also hold power in a way how their bodies are enjoyed. Besides, social norms outside the palace function as a panopticon that makes the inhabitants have self-awareness as they feel constantly monitored. Penelitian ini mengeksplorasi praktik relasi kuasa dan panoptikon sebagai mekanisme pendisiplinan dalam cerita pendek Istana Tembok Bolong karya Seno Gumira Ajidarma. ‘Istana tembok bolong’ dalam karya sastra ini merujuk pada sebuah tempat di dekat stasiun kereta api yang terpisahkan dari area luarnya oleh dinding yang berlubang, yang dianggap sebagai istana oleh masyarakat kelas bawah yang menempati ruang tersebut. Dengan menggunakan analisis Foucauldian, penelitian ini melihat fenomena ‘jual korek api’, yang merupakan isu utama dari cerita yang dibahas di sini. Fenomena yang terjadi di Yogyakarta pada tahun 1970-an tersebut menjadi media perwujudan kuasa terhadap pekerja seks jalanan. Hasil penelitian menunjukkan bahwa relasi kuasa beroperasi sebagai alat untuk mengendalikan tubuh, terutama tubuh perempuan. Hal ini karena tubuh perempuan menjadi komoditas sebagai akibat dari kapitalisme. Namun, dalam situasi tertentu, pekerja seks jalanan tersebut juga dapat memegang kekuasaan terkait bagaimana tubuh mereka dinikmati. Selain itu, norma-norma sosial di luar istana berfungsi sebagai panoptikon yang membuat penghuninya memiliki kesadaran diri karena mereka merasa terus-menerus diawasi.